THE IMPLEMENTATION OF SOCIAL WORK ASSIMILATION FOR PRISONERS - Diah Puspita Rini (IJCLS (Indonesian Journal of Criminal Law Studies), 2019)
This research explaining what the basic idea of the non-legal the need for the assimilation of the indonesian social work , explains how the implementation of assimilation for social work convicts in indonesia .This study adopted qualitative approaches and the kind of research juridical sociological perspective.Research focus is the basic idea of the non-legal the need for the assimilation of the indonesian social work , how the implementation of assimilation for social work convicts in indonesia .The source of the data used was primary and secondary data , data collection technique interviews and the literature study .The results of the study are the basic idea of the non-legal assimilation work society is coaching the assimilation of social work required for the inmate so that they will if can be brought in again by the community.This is in accordance with the purpose of criminal justice namely the theory which joint criminal the only but not the social work.The implementation of the assimilation of social work is in accordance with the applicable regulation .The factor that hinder from this research are rules that were not clear in tehnisnya regulate matters of the implementation of the assimilation of social work .Drawing conclusions of the study are the basic idea of the non-legal assimilation society is the work for the establishment of a convict so that they will not excommunicated if free the people and not repeat the appalling crimes he committed .The implementation of assimilation for social work convicts across indonesia in accordance with The Minister of Law and Human Rights of the Republic of Indonesia Number 3 Year 2018.